2014
DOI: 10.1002/jhet.1836
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient and Facile Synthesis of Isoxazolyl‐chromeno[4,3,2‐de]pyrimido[4,5‐h][1,6]napthyridinones

Abstract: The ceric ammonium nitrate‐catalyzed synthesis of (E)‐5‐amino‐N‐(3‐methyl‐5‐styrylisoxazol‐4‐yl)‐2‐arylchromeno[4,3,2‐de][1,6]napthyridin‐4‐carboxamides 5 was simply achieved upon the one‐pot four‐component reaction of isoxazolyl cyanoacetamide 1 with malononitrile 2, 2‐hydroxy acetophenone 3, and aromatic aldehydes 4 in ethanol. Compounds 5 on heating with acetic anhydride underwent tandem N‐acetylation and cyclocondensation involving intramolecular cyclization to afford the title compounds (E)‐11‐methyl‐12‐(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A different approach to tetraazaphenalenoid systems was developed by Shaw et al By condensing a substituted 1,3,6,9 a 1 -tetraazaphenalene with various bidentate nucleophiles, a range of extended nitrogen-rich frameworks were obtained ( C41.1 – 3 , Chart ). In 2014, a pentacyclic phenalenoid 141.3 was obtained in a uniquely concise synthesis by Rajanarendar et al The initial step involved a CAN-mediated multicomponent condensation of isoxazolyl cyanoacetamide 141.1 with malonodinitrile, benzaldehyde, and 2-hydroxyacetophenone, and was followed by the closure of the pyrimidinone ring with acetic anhydride (Scheme ).…”
Section: Phenalenoidsmentioning
confidence: 99%
“…A different approach to tetraazaphenalenoid systems was developed by Shaw et al By condensing a substituted 1,3,6,9 a 1 -tetraazaphenalene with various bidentate nucleophiles, a range of extended nitrogen-rich frameworks were obtained ( C41.1 – 3 , Chart ). In 2014, a pentacyclic phenalenoid 141.3 was obtained in a uniquely concise synthesis by Rajanarendar et al The initial step involved a CAN-mediated multicomponent condensation of isoxazolyl cyanoacetamide 141.1 with malonodinitrile, benzaldehyde, and 2-hydroxyacetophenone, and was followed by the closure of the pyrimidinone ring with acetic anhydride (Scheme ).…”
Section: Phenalenoidsmentioning
confidence: 99%
“…[11] In 2014, Rajanarendar et al reported the ceric ammonium nitrate-catalyzed fourcomponent reaction of malononitrile with isoxazolyl cyanoacetamide, 2-hydroxy acetophenone, and aromatic aldehydes for the synthesis of 2-arylchromeno[4,3,2-de][1,6]napthyridin-4carboxamides. [18] Recently, Mohammadi and Shaterian reported a γ-Fe 2 O 3 @SiO 2 -γ-aminobutyric acid-promoted the pseudo four-component of malononitrile with 2,4-dihydroxyacetophe-none, various aromatic aldehydes for the preparation of chromeno [4,3,2-de][1,6]naphthyridine derivatives. [19] Evidently, malononitrile and its derivatives as essential building blocks were used in multicomponent reactions due to the high reactivity of both the methylene and the cyano groups, which played an important role in the efficient construction of complex architectures.…”
mentioning
confidence: 99%